Reduction in remoteness distinctions and reconfiguration in the Bemba past tense1. (17th March 2016) - Kula, Nancy C.
Abstract: Bantu languages are well‐known for having multiple remoteness distinctions in both the past and the future. This paper looks at the 4‐way remoteness distinction of Bemba (central Bantu) showing that the system is undergoing change that is resulting in the loss of an intermediate past tense, by merger with the remote past. Two factors are central in driving this change; a merger of forms by tone loss and neutralisation and a shift in the scope of semantic function. Because the Bemba tense‐aspect system manifests the so‐called conjoint‐disjoint alternation, there is also some reconfiguration of the TA system that accompanies the merger. The different factors involved in this change are unified under a cognitive multi‐dimensional approach to tense, which is here extended to account for language change in tense systems.